Tourism managers’ perception of the impact of the emotional intelligence and resilience on organizational response to crisis - Burlea-Șchiopoiu, Adriana; Ogarcă, Radu-Florin; Mihai, Laurențiu-Stelian; Drăgan, Cristian Ovidiu (Journal of Business Economics and Management, 2023)
The study aims to analyze the synergies between internal factors (i.e., emotional intelligence and resilience) and external factors (i.e., governmental support) on the performance of tourism organizations in the post-disaster recovery phase. Data collected from the sample of 390 managers and owners in the tourism industry were analyzed using structural equation modeling with partial least squares (PLS-SEM) as an appropriate model method with variables containing multiple items and multiple causal relationships. Our findings reveal that the resilience of tourism organizations (during and post-pandemic crisis) is positively influenced by the employees’ and managers’ emotional intelligence and government support. Planned and adaptive resilience significantly affects organizational response to disruptive events and organizational performance. Our findings guide tourism organization managers and government authorities and help them make timely decisions based on the relationship between resilience, emotional intelligence, and governmental support during and after a crisis. Managers need to be aware of the importance of emotional intelligence in managing the business in uncertain/turbulent times and to be concerned with improving emotional intelligence for themselves and their employees. Our study is one of the first to analyze the pandemic’s effects in the post-disaster recovery phase and the first one focused on Romania’s tourism organizations. First published online 19 January 2024